The tendency to dehumanize, group malleability beliefs, and perceived threat from migrants in Hungary - Paskuj, Benedek; Orosz, Gábor (Frontiers in Psychology, 2022)
Examining the humanness attributed to several groups in a comprehensive Hungarian sample (N=505) at the height of the ‘European refugee crisis of 2015’ we found that Hungarians dehumanize Eastern ethnic groups more and Western ethnic groups less than they do to their own ethnic ingroup. Interestingly we also found that a general tendency of dehumanization is expressed across all national groups. This general tendency of dehumanization was strongly associated with threat perceived from migrants, but the relationship was mediated by group malleability – the belief that human groups can change and are not set in their ways irreversibly. Malleability beliefs were positively linked to higher tendencies to dehumanize and negatively linked to threat perceived from migrants. We discuss the theoretical and practical implications of the findings that point to the critical role of fixed mindsets about groups in the mechanisms linked to prejudice in a highly xenophobic Hungarian context.